Pengaruh Komunikasi Interpersonal Orang Tua dengan Anak dan Konsep Diri Siswa terhadap Motivasi Berprestasi Siswa dengan Motivasi Belajar Siswa sebagai Variabel Moderating (Studi pada Siswa Keturunan Etnis Tionghoa di SMK Negeri 1 Pekanbaru) - Retno Puji Pratiwi; Nurjanah Nurjanah; Welly Welly (Departement of Mathematics Education, 2023)
Forms of interpersonal communication can be established in a family that involves communication between individual parents and children. The age difference between parents and children is quite wide, causing differences in the periods experienced by both parties. It is possible that the differences in the periods experienced will provide different experiences in the form of attitudes and views between parents and children. Most parents always demand high achievements from their children in their education, without being accompanied by a democratic attitude and a lack of communication approaches, so that children's development is neglected, which ultimately affects children's learning achievements. This study aims to determine and analyze the effect of interpersonal communication between parents and children and students' self-concept on the achievement motivation of students of Chinese ethnic descent at SMK Negeri 1 Pekanbaru directly or moderated by student learning motivation. This research is included in causal research using descriptive quantitative methods. This research was conducted on students of Chinese ethnic descent at SMK Negeri 1 Pekanbaru. The time of the research started from January and February 20223. The population in this study were all students of Chinese ethnic descent at SMK Negeri 1 Pekanbaru, with the total number up to the 2022 school year - 2023 there are as many as 50 people. The sampling method uses the Saturated Sample method (Census Sample), so that the entire population is taken as a research sample. The data used is primary data through a questionnaire. The analytical tool used is Partial Least Square (PLS) Structural Analysis using Warp-PLS Software Version 5.0. The results showed that direct interpersonal communication between parents and children and students' self-concept had an effect on students' achievement motivation. Indirectly, student learning motivation has a significant positive moderating effect on the interpersonal communication relationship between parents and children and students' self-concept on student achievement motivation. However, student learning motivation is not a variable that can strengthen interpersonal communication relationships between parents and children and students' self-concept towards student achievement motivation. The contribution of interpersonal communication between parents and children, students' self-concept and the interaction of students' learning motivation on student achievement motivation is 96.6%, while the remaining 3.4% is the contribution of other variables not discussed in the research model.